VIDEO MARKETING IN EDUCATION: ATTRACTING APPLICANTS USING THE YOUTUBE SERVICE - Akhyadov, Elman; Goncharov, Vitaly; Makushkin, Sergey (Revista Inclusiones, 2020)
Internet communications have become an effective and popular tool for integrated marketing communications both to achieve a synergistic effect in large-scale marketing campaigns and to implement short-term tasks, communicate with target audiences, maintain reputation, promote the brand, etc. One of the most effective Internet marketing tools is video marketing on social networks. The article considers the problem of using video marketing as an Internet marketing tool to attract prospective university students (applicants) using the YouTube service, as well as presents a theoretical analysis of the patterns of occurrence and types of video marketing. Based on the results of an expert survey, the advantages and opportunities of using video marketing in the university's marketing campaign are determined, and recommendations on using video marketing to attract university applicants are provided.